COMPARISON OF INTERLEUKIN-6, PROCALCITONIN AND C-REACTIVE PROTEIN AS A DIAGNOSTIC BIOMARKER IN PATIENTS UROSEPSIS - Nursanto, Trisno Fajar; Soebadi, M. Ayodhia; Soebadi, Doddy M (Indonesian Urological Association, 2020)
Objective: To compare the diagnostic value of Interleukin-6 (IL-6), Procalcitonin (PCT) and C-Reactive Protein (CRP) in detecting urosepsis. Material & Methods: This study is an analytical descriptive cross-sectional study about the diagnostic value of IL-6, PCT, and CRP to determine the diagnosis of urosepsis. The study sample consisted of all SIRS patients with urological disorders. The entire sample was examined by IL-6, PCT, CRP, and urine culture as the gold standard diagnosis. Data were analyzed using 2x2 table analysis and ROC curve to obtain AUC value. Results: There are a total of 36 samples in this study. With a cut-off 140 pg/ml, IL-6 provides a sensitivity, specificity, Positive Predictive Value (PPV), Negative Predictive Value (NPV), Positive Likelihood Ratio (+LR) and Negative Likelihood Ratio (-LR) was 95.8%, 83.3%, 92%, 90%, 5.75, and 0.05 with AUC 90.8% (95% IK 80.2% -100%, p<0.001). Sensitivity and specificity for PCT with cut off 0.65 ng/ml were 75% and 83.3%. The sensitivity and specificity for CRP with cut off 41 mg/l was 70.8% and 58.3%. The AUC of PCT and CRP was 81.1% and 66.5%. Conclusion: IL-6 has the best diagnostic value followed by PCT and CRP in urosepsis cases. IL-6 can be used as a biomarker diagnostic of urosepsis.